Oral Desensitization to Penicillin for the Treatment of Pregnant Women with Syphilis: A Successful Program - Jéssica Dallé; Mauro Cunha Ramos; Mirela Foresti Jimenez; Fernanda Garcia Escobar; Vicente Sperb Antonello (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Gestational syphilis is a prevalent disease in Brazil and other low and medium income countries. Desensitization to penicillin is recommended for pregnant women with syphilis who are allergic to β-lactams. This is a descriptive study utilizing outpatient medical records from 2011 to 2015 from a mother and child hospital that is part of the national healthcare system in the South of Brazil, which performs an average of 3,600 birth assistances per year. All cases of pregnant women with syphilis and presumptive diagnosis of β-lactam allergy during the study period were included. The patients referred for desensitization originated from the hospital prenatal care service, as well as from municipal/state antenatal care services. Oral desensitization was performed in the obstetric emergency room, and adult and pediatric intensive care units were available at all times. Ten patients underwent desensitization during the period of study. Personal history of urticaria was the most common reaction that demanded desensitization. All patients tolerated the procedure well, and showed no adverse reactions.We report a successful program of oral desensitization. None of the patients presented adverse reactions or complications, a fact that corroborates the feasibility and safety of the desensitization protocol. Oral administration of penicillin comes at a low cost, and optimizes the use of time and resources.